EFEKTIVITAS MANAJEMEN KELAS DALAM PEMBENTUKAN KARAKTER SISWA - Monika Zalfa; Nadila; Nazwa Tauhida; Hinggil Permana (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to analyze the management of character education strengthening through a classroom-based approach at SDN Karawang Kulon I. Employing a qualitative method, data were obtained through observation and semi-structured interviews with fifth-grade teachers who implement character education directly in their classrooms. The findings reveal that active learning strategies such as diagnostic assessments, group learning, and kinesthetic approaches have been successfully integrated into daily teaching practices. Teachers emphasized the creation of a safe, positive, and inclusive classroom environment as essential for encouraging student participation and supporting character formation